Comparison of baseline ImPACT performance in amateur motocross riders to football and basketball athletes. (21st March 2018) - Sandel, Natalie K.; Worts, Phillip R.; Burkhart, Scott; Henry, Luke
ABSTRACT: Primary Objective : The American Motorcyclist Association requires professional riders to undergo baseline computerized neurocognitive testing (CNT) using the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) test for concussion management. It is recommended this practice be expanded to the amateur level, but limited research has explored whether baseline testing is necessary for youth when normative data is available. This study evaluates the utility of baseline testing for amateur riders by comparing their performance to those of traditional youth sports comprising normative datasets. Design/Methods : An cross-sectional study comparing amateur motocross ( N = 100) riders matched by age and sex to football ( N = 100) and basketball ( N = 100) athletes performance on baseline ImPACT testing. Results : ANCOVAs revealed a significant medium effect of group on measures of visual motor speed ( F = 11.25, p < 0.001) and reaction time ( F = 13.61, p < 0.001). Post hoc analyses revealed that motocross riders were significantly slower compared to football and basketball athletes. There were no significant differences ( p > .05) between sport on measures of memory or symptoms. Conclusions : Youth motocross riders performed significantly slower on speed measures compared to football and basketball athletes, providing preliminary support for the expansion of baseline ImPACT testing to the amateur level.